Methods of rolled copper wire properties improvement - Duriagina, Zoya; Dvorianyn, Khristyna; Shvachko, Sergiy; Pleshakov, Eduard; Tepla, Tetiana (Lviv Polytechnic Publishing House, 2015)
Hot cracks of rolled copper are the most wide spread type of discards under continuous casting which are eliminated with difficulty. In industrial production of rolled copper wire at the plants of Ukraine the amount of oxygen in the obtained rods does not exceed the standard values. In this paper it is proposed to subject the melt to ultrasonic treatment to degassing process and the formation of homogeneous, dispersive sub dendrite structure of the rolled copper.
Keywords: rolled copper; hydrogen; hot cracks; wire; pores